EXPLORING THE INTERPLAY OF ENVIRONMENTAL DYNAMISM, SUPPLY CHAIN AMBIDEXTERITY, INCENTIVE GOVERNANCE AND DIGITAL QUALITY MANAGEMENT SYSTEM IN ACHIEVING HEALTHCARE SUPPLY CHAIN SUSTAINABILITY - Atif Munir; Sehar Gulzar; James John; Nadeem Ul Hassan Khan; Saqib Nabi; Memoona Tahir (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the intricate interplay of environmental dynamism (ED), supply chain ambidexterity (SA), and incentive governance (IG) in shaping the sustainability of healthcare supply chains (HSC). The research, prompted by vulnerabilities revealed during the COVID- 19 pandemic and heightened by demographic shifts and healthcare challenges, underscores the necessity for adaptable and customized supply chain structures. Supply chain ambidexterity emerges as a crucial concept, balancing operational efficiency with innovation. Incentive governance aligns stakeholder interests, and the adoption of technophilia and blockchain presents transformative opportunities. The study aims to guide healthcare organizations, policymakers, and stakeholders in fostering sustainable practices amid unprecedented challenges. The methodology employs purposive sampling, targeting healthcare supply chain managers and employees with supply chain knowledge. A questionnaire, distributed through Google Forms, addresses six key constructs adapted from validated sources, receiving 108 responses. Hypotheses explore relationships and interactions guided by a theoretical framework. Demographic analysis reveals diverse participant characteristics. Model validation involves convergent validity and composite reliability assessments. The findings indicate strong factor loadings, reliable data, and valid measures. Discriminant validity, assessed through Fornell-Larcker criterion and factor cross-loading data, confirms the distinctiveness of constructs. The meticulous application of these validation techniques ensures methodological integrity. Hypothesis testing examines the impact of environmental dynamism on healthcare supply chain sustainability, considering mediating and moderating factors. Results affirm significant effects, emphasizing the role of supply chain ambidexterity, incentive governance, and digital quality management. Effect size estimations categorize impacts as medium to large, underscoring the relevance of the explored relationships. The study contributes to bridging knowledge gaps, offering actionable insights to enhance healthcare supply chain adaptability, efficiency, and sustainability amid dynamic environmental conditions and technological advancements. Researchers and practitioners can rely on these findings, grounded in a comprehensive and rigorous approach to measurement and analysis.